¿Qué aportan las técnicas de exposición a la efectividad de la terapia cognitivo-conductual con parches de nicotina para dejar de fumar? - García Vera, María Paz; Sanz, Jesús (Psicooncología, 2006)
Objective: To examine whether cue-exposure therapy increases the effectiveness of a multicomponent smoking cessation program that combines cognitive-behavioral techniques with nicotine patches. Method: Pre-post-follow-up quasi-experimental study of two groups, one group of 22 smokers that received a multicomponent group smoking cessation program that combined cognitive-behavioral techniques with nicotine patches and other group of 26 smokers that received a similar program that also included in vivo exposure to smoking-related cues and contexts and daily self exposure homework. Results: The program with cue-exposure therapy showed higher abstinence rates at post-treatment, 1-month follow-up, 6-month follow-up and one-year follow-up than those showed by the program without cue-exposure therapy (65,4%, 65,4%, 66,7% and 66,7%, respectively, versus 59,1%, 59,1%, 40,9% and 36,4%), however, the differences were not statistically significant. Conclusions: It seems that cue-exposure therapy does not significantly increase the abstinence rates of a multicomponent smoking cessation program that combines cognitive-behavioral techniques with nicotine patches. However, this conclusion should be taken with caution because the present study used a cuasi-experimental design (instead of an experimental one) and is based on a small number of smokers. In this sense, it is likely that this study lacked statistical power since differences so large as the 25-30 percentage points found at the six-month and one-year follow-ups did not reach statistical significance.